2021
DOI: 10.3390/jcm10132754
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Role of PCDH19 in Clustering Epilepsy by Exploiting Patient-Specific Models of Neurogenesis

Abstract: PCDH19-related epilepsy is a rare genetic disease caused by defective function of PCDH19, a calcium-dependent cell–cell adhesion protein of the cadherin superfamily. This disorder is characterized by a heterogeneous phenotypic spectrum, with partial and generalized febrile convulsions that are gradually increasing in frequency. Developmental regression may occur during disease progression. Patients may present with intellectual disability (ID), behavioral problems, motor and language delay, and a low motor ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
(96 reference statements)
1
19
0
Order By: Relevance
“…Moreover, comparing the differentiation process of mixed iPSCs with control ones, it emerged that, as in the pathological condition, neural rosettes appeared earlier and showed a disorganized structure with a reduced lumen [ 59 ], in line with the findings by Homan and co-workers [ 22 ]. To investigate the mechanism underlying this early differentiation, the same authors showed that PCDH19 loss of function results in significant centrosome hyper-amplification in mitotic iPSCs and an increase in asymmetrical cell division by progenitor cells close to the center of the rosettes [ 59 ]. This altered cell behavior is most probably responsible for the increase in cell differentiation and defective neural progenitor cell proliferation [ 62 ].…”
Section: Ipscs As a Model System For Studying Pcdh19-cesupporting
confidence: 58%
See 2 more Smart Citations
“…Moreover, comparing the differentiation process of mixed iPSCs with control ones, it emerged that, as in the pathological condition, neural rosettes appeared earlier and showed a disorganized structure with a reduced lumen [ 59 ], in line with the findings by Homan and co-workers [ 22 ]. To investigate the mechanism underlying this early differentiation, the same authors showed that PCDH19 loss of function results in significant centrosome hyper-amplification in mitotic iPSCs and an increase in asymmetrical cell division by progenitor cells close to the center of the rosettes [ 59 ]. This altered cell behavior is most probably responsible for the increase in cell differentiation and defective neural progenitor cell proliferation [ 62 ].…”
Section: Ipscs As a Model System For Studying Pcdh19-cesupporting
confidence: 58%
“…In particular, Homan and co-workers suggested that the coexistence of cells expressing mutated and wild-type PCDH19 proteins was associated with a loss of apical-basal polarity and an increased rate of neuronal differentiation. In a recent work [ 59 ], Borghi and co-workers confirmed accelerated cortical differentiation in vitro using iPSC derived from a mosaic male patient (PCDH19-iPSCs). As in [ 22 ], PCDH19-iPSCs were mixed with wild-type iPSCs to recreate the mosaic condition.…”
Section: Ipscs As a Model System For Studying Pcdh19-cementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is possible that PCDH19 mutations can alter the correct positioning of the mitotic spindle causing a higher number of asymmetric divisions leading to accelerating neural differentiation. An altered equilibrium between symmetric vs. asymmetric cell division may contribute to the pathogenesis of the disease ( 11 ). The synaptogenesis role of PCDH19 was confirmed by Mincheva-Tasheva et al who showed disruption of excitatory synaptic contacts between PCDH19-knock-out and wild-type neurons in “mosaic” neuronal cultures ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…These experiments were performed in MCF-7 cancer cells, which may not be the best model for investigating the consequences of PCDH19 variation that causes heterogenous neurological phenotypes [ 2 ]. Other immunofluorescence studies in proliferating iPSCs and polarized cells of the neural rosette lumen show that PCDH19 localises to the mitotic spindle pole of the dividing cells and affects its formation, suggesting that PCDH19 may play a role in regulating asymmetric versus symmetric cell division during neurogenesis [ 56 , 57 ]. Taken together, these data indicate differences in the localisation and possible function of PCDH19 in different cell types and at different cell cycle stages.…”
Section: Role Of Steroids In Cementioning
confidence: 99%